Use of new generation single nucleotide polymorphism genotyping for rapid development of near-isogenic lines in rice - Boualaphanh, Chanthakhone; Daygon, Venea D.; Calingacion, Mariafe N.; Sanitchon, Jarawit; Jothityangkoon, Darunee; Mumm, Roland; Hall, Robert D.; Fitzgerald, Melissa A. (Wiley, 2011)
Studies aimed at determining gene function or identity are greatly facilitated by introgression lines and phenotyping tools. However, developing introgression lines can take six to eight generations to reach the desired level of background purity and homozygosity. The objective of this study was to use new generation genome‐wide single nucleotide polymorphism (SNP) genotyping, along with a molecular marker for the allele of interest, and a relevant phenotyping tool, to develop research populations with just four generations of backcrossing. Two populations were created for future research on aroma in rice (Oryza sativa L.): one derived from two indica parents and the other from one indica and one tropical japonica parent. The same recurrent parent was used for both populations. Single nucleotide polymorphism genotyping of BC4F2 progeny selected previously on the basis of either a marker for fragrance or the presence of the fragrant compound and on the basis of morphological similarity to the recurrent parent showed that donor introgression ranged from <0.1% up to 35%. Single nucleotide polymorphism genotyping allowed the selection of a set of fragrant lines with minimal additional donor introgression after four generations. Metabolite profiling of the volatile blend in grains from parents and selected introgression lines showed that selected lines clustered with the recurrent parent. These new genotyping and phenotyping techniques enabled valuable genetic stocks to be developed in a short time for use in biochemical and genetic projects on fragrance in rice.